THE RELATIONSHIP OF PHYSICAL ACTIVITY, GADGET USE, AND SLEEP TIME TO ADOLESCENT OBESITY - Anwar Pasaribu; Sunarto Kadir; Flora Ninta Tarigan; Irwan (Scholar Express Journals, 2023)
Overweight and obesity are a global health problem for both children and adults. The highest number of overweight and obese people in Gorontalo Province in 2017, in all age groups, was highest in Gorontalo City. This study aims to determine the relationship between physical activity, gadget use, and sleep time. This type of research uses a quantitative method with Observational analysis with a Cross-Sectional research design using the Spearman test. The population included in the study were all SMA Negeri 2 Kota Gorontalo students, totaling 1149 students. Sampling was carried out non-randomly using a purposive sampling technique determined using the Slovin formula. So, the sample size for this study was 92 students. The research showed an influence between physical activity and obesity in adolescents with a P-value = 0.010 ( <0.05). Based on the results of the study at SMA N 2 Gorontalo City, it was found that there was an influence between playing gadgets and the incidence of obesity in adolescents with a P-value = 0.009 (><0.05). Based on the results of research at SMA N 2 Gorontalo City, it was found that there was an influence between sleep time and the incidence of obesity in adolescents with a P-value = 0.000 (><0.05). The conclusion is that physical activity, use of gadgets, and sleep time are related to obesity in adolescents.>
Keywords: Obesity; Physical activity; Use of Gadgets; Bedtime